Pelatihan Self-Management Sebagai Upaya Pencegahan Perilaku Fear of Missing Out (FoMO) Pada Kalangan Siswa SMK Melalui Experiential Learning - Flurentin, Elia; Setiyowati, Arbin Janu; Prihatiningsih, Riskiyana; Pratiwi, Awalya Siska; Munir, Ah Fahri (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
The Fear of Missing Out (FoMO) phenomenon is increasingly troubling, especially for teenagers who actively use social media, such as Vocational High School (SMK) students. They are in an identity-seeking phase and tend to feel the need to be constantly connected to their social environment, especially on online platforms. While social media facilitates interaction with peers, overexposure can trigger anxiety and feelings of insecurity, which in turn impacts their mental and emotional health. The effects of FoMO are also seen in declining academic performance and social skills, as students spend more time paying attention to the lives of others rather than focusing on their personal tasks and achievements. To help students overcome FoMO, the service program at SMK Nasional Malang applies the experiential learning approach as a learning method that emphasizes the development of self-management. Through this training, students are trained to manage emotions, utilize personal experience as a learning medium, and cultivate the ability to control themselves from the temptation of constantly checking social media. Experiential learning strategy has been proven to improve students' abilities in cognitive and affective aspects, such as emotion management and teamwork. This approach is expected to reduce the negative impact of FoMO and strengthen students' awareness of the importance of balance between the online world and real life. This service includes socialization, case analysis, and training modules as practical steps to guide students in practicing self-management in the school environment. From the implementation of this service activity until completion, students are expected to not only be able to control their own behavior but also be able to share this positive influence with their peers. Hopefully, through school support and ongoing training, students can develop adequate digital literacy and self-management skills to cope with social media pressure and improve overall quality of life.